PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA (Studi pada Karyawan RSUD Tugurejo Semarang) - Wiwin Eriyan Tanti, 12.05.51.0028; Priyono, Bambang Suko (Students Journal of Economic and Management, 2016)
The purpose of the study was to analyze the effect of compensation and work environment on employee performance with work motivation as mediation. The study uses five hypotheses. The population in the study is all employees of Hospitalof Tugurejo Semarang. The sample use 98 people. The sampling technique used purposive sampling. The criteria for the sample were employees having been appointed as civil servants and have Â minimum tenure of 3 years. The analysis tool used is multiple linear regression. The results of the analysis concluded that: Compensation positively affect on work motivation. The working environment positively affect on work motivation, Compensation positively influence on employee performance, working environment positively influence on employee performance. Work motivation positively influence on employee performance. Work motivation does not mediate the affect of compensation to employee performance. Work motivation does not mediate the affect of the work environment on employee performance Â Keywords: compensation, work environment, motivation and performance of employees